Impacts of property tax policy on Illinois farmers - Bodine, William D. (Kansas State University, 2013)
Since 1977, the State of Illinois has used a use-value method of assessing farmland for property taxes. The method establishes farmland value by determining a five year average of net income from the land that is capitalized using a five year average interest rate. Other real estate in Illinois follows a different procedure for assessment. For example, residential property is assessed at one-third of its market value. The differences among the methods of assessment for farmland and other types of real estate, along with recent market increases in farmland values and a strong agriculture economy, have led some to question the current method of farmland assessment. The objective of this thesis is to determine the financial impact to farmers resulting from changing from the current use-value assessment of farmland to market-value assessment. This is accomplished with two sub-objectives: determine the potential change in farmland values that could occur and to determine the impact on net farm income that could occur if property tax policy was changed to market-value assessment. To accomplish the first sub-objective, a model was developed to estimate farmland values in Illinois based on the current use-value assessment property tax policy. This model was then adjusted to estimate farmland values under a market-value assessment property tax policy. The models demonstrated that farmland values could fall 53 percent, or an average of $2,548 per acre, in the year immediately following implementation of a tax policy change. Once farmland values stabilize after implementation of the tax policy change, farmland values would be 30 percent less, or an average of $1,875 per acre less, under market-value assessment than under use-value assessment. A simulation of net farm income over a ten year time frame was then conducted to estimate the potential change in net farm income that could occur from a change to market-value assessment. Like farmland values, the greatest impact to net farm incomes occur in the first year market-value assessment is implemented. Farmland values and the resulting property taxes then stabilize during later years. The simulation of net farm income over a ten year time frame estimates that net farm income would be 8 percent lower per year, or a reduction in net farm incomes of an average of $12,721 per year, under market-value assessment. The analysis also showed the potential for an average of a 2 percent increase in the probability that net farm income would fall below zero over the simulation time frame. The analysis demonstrates that a change from use-value assessment to market-value assessment of farmland could reduce farmland values and net farm incomes. Such a change in policy is not in the best interests of farmers or the agriculture industry in Illinois, as the reduced values and incomes would have wide reaching negative consequences that could reach beyond farmers and farmland owners.
Keywords: Property Tax; Agricultural use-value; Simulation; Discounting; Agriculture, General (0473); Economics, Agricultural (0503); Political Science (0615); Public Administration (0617)